2022
DOI: 10.1063/5.0077707
|View full text |Cite
|
Sign up to set email alerts
|

A general equation of state for high density matter from thermodynamic symmetry

Abstract: A general and simple equation of state (EOS) is a rich source for research and discussion. Experience shows that high-density matter exhibits simple regularities and some “universal” EOSs have been established. Here, we present an ideal dense matter EOS that is symmetric to the ideal gas EOS by means of Oettingen's dual approach. The ideal dense matter EOS makes no assumptions about the structure of matter and is, therefore, general. Thermodynamic symmetry requires that the ideal dense matter EOS has better ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The ideal gas EOS in P-S-T form is where is the specific heat at constant pressure and the subscript 0 denotes a given thermodynamic state. The ideal dense matter EOS in P–V-T form is 13 where is the specific work at constant temperature, defined as 14 …”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The ideal gas EOS in P-S-T form is where is the specific heat at constant pressure and the subscript 0 denotes a given thermodynamic state. The ideal dense matter EOS in P–V-T form is 13 where is the specific work at constant temperature, defined as 14 …”
Section: Modelingmentioning
confidence: 99%
“…As we know, the ideal gas EOS, is a well-known low-density limiting model and all matter shares this simple relation at ultra-low densities 12 . Recently, it has been found that there is thermodynamic symmetry between the features of the two extremes of density, and thus an ideal dense matter EOS symmetric to the ideal gas EOS was presented 13 where is a constant, called the ideal dense matter constant. It is a high-density limiting model and all matter shares this simple relation at ultra-high densities 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the above view is now being challenged. Recent studies have found that the thermodynamic properties of matter, in themselves, have symmetry [8,9]. By contrast, the thermodynamic properties are directly dependent on the structure of the substance and the thermodynamic state it is in.…”
Section: Introductionmentioning
confidence: 99%
“…Note also that its modification 13 leads also to the Murnaghan equation initially derived for highly compressive isotropic solids. Recently, there were some attempts to address Tait's parameters from general thermodynamic points of view considering the ultra-high pressure range 14 and its interpolating to the low-pressure limiting state 15 as well as from the theory thermodynamic fluctuations 16 that allows building the Tait-like shaped Fluctuations Theory-based Equation of State (FT-EOS), which extrapolates data obtained at ambient pressure to the elevated one up to some hundred Megapascals for a wide range of liquid's classes, including polar, and ionic liquids and liquid mixtures [17][18][19] . However, the latter fails when the pressure tends to GPa range; this has been argued as the transition of liquid's bulk modulus to the behaviour typical for isotropic solids (Murnaghan's equation) 20 .…”
mentioning
confidence: 99%